1994
DOI: 10.1007/bf02506819
|View full text |Cite
|
Sign up to set email alerts
|

An advocacy intervention program for women with abusive partners: Six‐month follow‐up

Abstract: Presented the 6-month follow-up findings of an experimental intervention designed to provide postshelter advocacy services to women with abusive partners. The intervention involved randomly assigning half the research participants to receive the free services of an advocate, 4 to 6 hours per week, for the first 10 weeks postshelter. One hundred forty-one battered women were interviewed about their experiences immediately upon their exit from a domestic violence shelter: 95% of the sample were interviewed 10 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 34 publications
3
63
0
1
Order By: Relevance
“…Families saw their advocates for a mean of 10 hours a week, averaging 5 hours with the children and an additional 2.7 hours with the women. The basis of advocacy and the content of the sessions was similar to that of earlier intervention studies by Sullivan and her colleagues [125][126][127][128][129] (reported under Studies included in our previous review below). An important part of the intervention was ensuring that the advocate was no longer needed after 16 weeks.…”
Section: Studies Published Since Our Previous Reviewmentioning
confidence: 86%
See 3 more Smart Citations
“…Families saw their advocates for a mean of 10 hours a week, averaging 5 hours with the children and an additional 2.7 hours with the women. The basis of advocacy and the content of the sessions was similar to that of earlier intervention studies by Sullivan and her colleagues [125][126][127][128][129] (reported under Studies included in our previous review below). An important part of the intervention was ensuring that the advocate was no longer needed after 16 weeks.…”
Section: Studies Published Since Our Previous Reviewmentioning
confidence: 86%
“…11 In two separate randomised controlled studies (a pilot and a main study) by Sullivan and colleagues, [125][126][127][128][129] undergraduate psychology students were trained to provide 10 weeks of community-based advocacy to severely abused women exiting from refuges. Advocacy was tailored to the individual women's needs to help them to access community resources (such as housing, employment, legal assistance, transport and childcare), as well as empowering the women themselves.…”
Section: Studies Included In Our Previous Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Two interventions show treatment gains for children and mothers leaving domestic violence shelters: The Learning Club (Sullivan, Bybee, & Allen, 2002;Sullivan, Campbell, Angelique, Eby, & Davidson, 1994) and Project SUPPORT (Jouriles et al, 2001;McDonald, Jouriles, & Skopp, 2006). Both involve an advocacy and a mentoring component for the mother that includes modeling of appropriate child management strategies, empowerment and support, and assistance in acquiring resources.…”
Section: Violence Exposure Treatments Evaluating Other Child Outcomesmentioning
confidence: 99%